Legal Challenges in Multinational Corporate Governance: Perspectives of International Legal Universalism and Local Particularism - Ahmad Fauzan; Siti Wahyuni (Candela Edutech Indonesia, 2026)
Unlike prior studies that treat the universalism-particularism debate primarily as a theoretical dichotomy to be resolved, this article offers a distinctive contribution by integrating Lon Fuller’s procedural natural law theory with Franz and Keebet von Benda-Beckmann’s theory of legal pluralism into a unified normative-doctrinal framework for analyzing multinational corporate governance. The main challenge faced by multinational companies is how they can navigate the tension between the perspective of international legal universalism, which demands consistency and uniformity, and the reality of legal particularism inherent in each jurisdiction. This study aims to answer the question of how multinational companies respond to the legal challenges arising from the intersection between the principles of international legal universalism and local legal provisions in various jurisdictions. This research is normative doctrinal legal research with statutory and conceptual approach. This study shows that MNCs' responses to global legal complexity involve dynamic strategies of convergence and divergence. Facing the dilemma between universalism and particularism, MNCs actively balance demands for uniform global governance standards with the need to adapt to cultural norms and values, as well as local legal systems. Convergence efforts are evident in the adoption of international best practices and centralized compliance frameworks, driven by the need to attract investors and maintain reputations. However, divergence occurs when MNCs must adapt their practices to local cultures, institutions, and even informal norms, often presenting challenges for local managers.